2018
DOI: 10.3390/pathogens7010024
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics of Mycobacterium: An Emerging Landscape for Drug Discovery

Abstract: Mycobacterium tuberculosis (Mtb) exhibits remarkable metabolic flexibility that enables it to survive a plethora of host environments during its life cycle. With the advent of bedaquiline for treatment of multidrug-resistant tuberculosis, oxidative phosphorylation has been validated as an important target and a vulnerable component of mycobacterial metabolism. Exploiting the dependence of Mtb on oxidative phosphorylation for energy production, several components of this pathway have been targeted for the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 202 publications
(275 reference statements)
0
58
0
3
Order By: Relevance
“…BDQ is the first-in-class ATP synthase inhibitor which displays high selectivity toward mycobacterial ATP synthase and therefore renders the bacterium low on energy. Furthermore, it has been reported that, upon BDQ treatment, major metabolic alterations occur in the cell and several biosynthetic processes are downregulated (19,25). Hence, we were tempted to explore if the atpD-knockout strain mimics BDQ-treated wild-type M. smegmatis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BDQ is the first-in-class ATP synthase inhibitor which displays high selectivity toward mycobacterial ATP synthase and therefore renders the bacterium low on energy. Furthermore, it has been reported that, upon BDQ treatment, major metabolic alterations occur in the cell and several biosynthetic processes are downregulated (19,25). Hence, we were tempted to explore if the atpD-knockout strain mimics BDQ-treated wild-type M. smegmatis.…”
Section: Discussionmentioning
confidence: 99%
“…ATP synthase is essential for mycobacterial survival in both the replicating and dormant states (18,19,25). Thus, inhibition of this essential pathway via any means is, in all likelihood, bound to affect the key metabolic pathways in the cell.…”
mentioning
confidence: 99%
“…Interestingly, targeting cytochrome P450 enzymes in M. tuberculosis has also been proposed as the source of a potential new class of drugs for treating MDR-TB [ 78 ]. Similarly, targeting oxidative phosphorylation (NADH dehydrogenase, menaquinone biosynthesis, terminal oxidase, and ATP synthase) with specific inhibitors (phenothiazine derivatives, DG70, imidazopyridine amides, and diarylquinolines), in combination with antitubercle drugs, is an exciting novel avenue for short-term and effective treatment [ 79 ]. Notably, inhibiting bacterial oxidative phosphorylation may also result in limiting the formation of “persisters” in the host.…”
Section: Potential New Tb Therapies Targeting the Oxidant : Antioxmentioning
confidence: 99%
“…Additionally, the MK/MKH can also be reduced by alternative electron donors, e.g., via the succinate dehydrogenase (SDH). Electrons can be transferred directly from the MK/MKH to the cytochrome bc 1- aa 3 complex or alternatively, the oxygen can be reduced by a cytochrome bd -type terminal oxidase, which directly accepts electrons from the MK/MKH (Black et al, 2014 ; Bald et al, 2017 ; Iqbal et al, 2018 ). The proton gradient generated through oxidative phosphorylation leads to ATP synthesis via the ATP synthase which is responsible for the conversion of the electrochemical potential energy generated by the PMF into chemical energy in the form of ATP (Feniouk et al, 2007 ).…”
Section: Tuberculosis Biology Challenges: Focus On Energymentioning
confidence: 99%